LED-fluorescence microscopy for diagnosis of pulmonary tuberculosis under programmatic conditions in India. - Lord Wasim Reza (Public Library of Science (PLoS), 2013)
Background Light-emitting diode fluorescence microscopy (LED-FM) has been shown to be more sensitive than conventional bright field microscopy using Ziehl-Neelsen (ZN) stain in detecting sputum smear positive tuberculosis in controlled laboratory conditions. In 2012, Auramine O staining based LED-FM replaced conventional ZN microscopy in 200 designated microscopy centres (DMC) of medical colleges operating in collaboration with India's Revised National Tuberculosis Control Programme. We aimed to assess the impact of introduction of LED-FM services on sputum smear positive case detection under program conditions. Methods This was a before and after comparison study. In 15 randomly selected medical college DMCs, all presumptive TB patients who underwent sputum smear examination in the years 2011 (before LED-FM) and 2012 (after LED-FM) were compared. An additional 15 comparable DMCs that implemented conventional ZN sputum smear microscopy were also selected for comparison between 2011 and 2012. Results The proportion of presumptive TB patients (PTP)found sputum smear positive increased by 30%- from 13.6% (3432/25159) in 2011 to 17.8% (4706/26426) in 2012 (P value <0.01) in the sites that implemented LED-FM microscopy, whereas in DMCs where the ZN staining procedure is followed the proportion of sputum smear positive had remained unchanged (13.0%versus 12.6%;P value0.31). Conclusion Use of LED-FM significantly increased the proportion of smear positive cases among presumptive TB patients under routine program conditions in high workload laboratories. The study provides operational evidence needed to scale-up the use of LED-FM in similar settings in India and beyond.